Cantwell, Theresa Squires. Black and white photograph of four women and one man from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: Eileen Druken (Squires), Will Squires, Theresa "Tess" Murphy (Squires), Margaret Jane Squires (Thorpe), Amelia "Mell" Murphy (Squires).